Pengaruh Penggunaan Limbah Kantong Plastik Sebagai Bahan Tambah dalam Campuran Ac – Base - Dody Pagewang; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2020)
This study was intended to determine the effect of using plastic bag waste as an added ingredient in the Ac-Base mixture. The method in this research is to conduct a series of testing the characteristics of coarse, fine aggregate, filler and asphalt then design the composition of the AC-BASE mixture and Marshall test to obtain the mixture characteristics by Marshall Immersion testing to obtain the remaining strength index (IKS) using optimum asphalt content. The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Civil Engineering, Indonesian Christian University, Paulus Makassar, showed that the characteristics of pavement materials in the form of aggregates from the Jeneberang River which were added with plastic bag waste met 2018 Highways Quality Specifications as road pavement coating materials. Through the Marshall test obtained the characteristics of AC-BASE mixture with plastic content 0.00%, 0.50, 1.00%, 1.50%, 2.00%. The results of the Marshall Immersion test of AC-BASE mixture with an optimum plastic content of 2.00% obtained a Residual Strength Index (IKS) of 98.31% which met the General Specifications of the 2018 Highways which is 90%.